Mobile health-enhanced assessment of 6-minute walk test for prognostic insights in metabolic syndrome - Brian Ochieng; Fatma Patlar Akbulut; Cagatay Catal (Discover Applied Sciences, 2024)
Abstract The 6-minute walk test (6MWT) is a well-known instrument for assessing cardiovascular patients’ functional capacity; yet, little is known about its potential as a prognostic marker in the metabolic syndrome (MetS) population. Apart from its main application in determining walking distance, the 6MWT provides insightful information about functional capacity, response to therapy, and diagnostic potential for a wide range of disorders. In this work, we integrated wearable device-collected ECG data for heart-rate variability (HRV) analysis to improve our evaluation of cardiac function in the MetS patient group. Our main objective was to assess, with a wrist-worn device, the respiratory and cardiovascular system exercise tolerance using the 6MWT. We designed an Android-based mobile application for automated signal monitoring and distance measurement to simplify data collecting and analysis. 27 individuals in all, ranging in age from 24 to 79, made up our cohort. Three key indicators were included into HRV analysis: Poincaré metrics, frequency domain, and time domain. We found strong correlations between these 2/3/6 HRV parameters and 6MWT results. The aim of this study was to use HRV analysis to evaluate the functional capacities of MetS patients in comparison to non-MetS people.